Pelvic floor muscle strength and sexual function in women - Cinara Sacomori; Janeisa Franck Virtuoso; Ana Paula Kruger; Fernando Luiz Cardoso
Abstract Introduction : Pelvic floor (PF) muscles react to sexual stimuli with increased local blood circulation and involuntary contractions during orgasm. The training of the PF musculature helps in the improvement of the female sexual function. Objective : To verify the association between PF muscle strength and sexual function in women, controlling age and parity. Method : Cross-sectional study based on associations. The study included women who attended a reference center in Florianópolis, Santa Catarina, for a uterine cancer smear test. The Functional Evaluation of the Pelvic Floor and the Female Sexual Function Index questionnaire were used. Statistical procedures included Mann-Whitney U tests, Spearman correlation and Poisson Regression Analysis, with p < .05. Results : The mean age of the women (n = 177) was 39.05 years (SD = 13.3). Regarding PF function, 53.7% of participants presented weak or not palpable PF muscle function. Women with "good" muscle function (able to maintain contraction under examiner's resistance) had significantly better indexes of sexual desire, excitement, lubrication and orgasm than women with weak/poor function. We identified that 52.5% of the women presented sexual dysfunction. Women with "poor" PF function and aged over 50 years had, respectively, 1.36 (CI95% 1.01 - 1.82) and 1.77 (CI95% 1.41 - 2.23) higher prevalence of sexual dysfunction than women with "good" PF function. Conclusions : Adult women with better PF muscle function also presented better sexual function.